THE EFFECTS OF DIGITAL TRANSFORMATION, ESG DISCLOSURE, AND CORPORATE GOVERNANCE ON CORPORATE FINANCIAL DISTRESS THROUGH OPERATIONAL RISK AND FINANCING CONSTRAINTS - Faridah; Sitti Mujahida Baharuddin; Herminawaty; Nurhidayanti s; Thanwain; Muhammad Azizurrohman (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2026)
This study examines the effects of digital transformation, ESG disclosure, and corporate governance on corporate financial distress, with a focus on the mediating roles of operational risk and financing constraints. Using panel data from non-financial firms listed on the Indonesia Stock Exchange over the period 2018 to 2024, the study applies fixed effects regression and bootstrap mediation analysis to test the proposed relationships. The results show that ESG disclosure and corporate governance significantly reduce financial distress, while digital transformation exhibits a positive direct effect, reflecting transitional costs and complexity during early adoption stages. However, the mediation analysis reveals that digital transformation, ESG disclosure, and corporate governance indirectly improve financial stability by reducing operational risk and financing constraints. Both mediating variables are found to be significant determinants of financial distress, confirming the importance of internal risk conditions and access to external financing. The findings support a dual-channel framework, demonstrating that financial distress is shaped not only by firm characteristics but also by underlying transmission mechanisms. This study contributes to the literature by integrating multiple theoretical perspectives and providing evidence from an emerging market context. The results offer practical implications for firms and policymakers in enhancing financial resilience through improved governance, transparency, and digital capability.